2018
DOI: 10.1007/s13167-018-0136-8
|View full text |Cite
|
Sign up to set email alerts
|

Mental stress as consequence and cause of vision loss: the dawn of psychosomatic ophthalmology for preventive and personalized medicine

Abstract: The loss of vision after damage to the retina, optic nerve, or brain has often grave consequences in everyday life such as problems with recognizing faces, reading, or mobility. Because vision loss is considered to be irreversible and often progressive, patients experience continuous mental stress due to worries, anxiety, or fear with secondary consequences such as depression and social isolation. While prolonged mental stress is clearly a of vision loss, it may also aggravate the situation. In fact, continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
137
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(157 citation statements)
references
References 219 publications
(179 reference statements)
7
137
1
12
Order By: Relevance
“…Results from a total of 11,834 participants were analyzed (5,876 men and 5,958 women; mean age 54.4 ± 11.0 years), of whom 1,089 (9.2%) were diagnosed as having AMD. Early AMD (stages 1-3) was present in 95.2% (1037) of the participants with AMD, stage 1a, 21.1% (230), stage 1b, 49.0% (534), stage 2a, 13.0% (142), stage 2b, 3% (39), stage 3, 8.5% (92), late AMD (stages 4a + 4b) was present in 4.8% (52) of the participants, stage 4a, 4.2% (46), stage 4b, 0.6% (6). Individuals in the AMD group were older than those in the control group (61.8 ± 9.9 years vs. 53.6 ± 10.8, respectively, p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…Results from a total of 11,834 participants were analyzed (5,876 men and 5,958 women; mean age 54.4 ± 11.0 years), of whom 1,089 (9.2%) were diagnosed as having AMD. Early AMD (stages 1-3) was present in 95.2% (1037) of the participants with AMD, stage 1a, 21.1% (230), stage 1b, 49.0% (534), stage 2a, 13.0% (142), stage 2b, 3% (39), stage 3, 8.5% (92), late AMD (stages 4a + 4b) was present in 4.8% (52) of the participants, stage 4a, 4.2% (46), stage 4b, 0.6% (6). Individuals in the AMD group were older than those in the control group (61.8 ± 9.9 years vs. 53.6 ± 10.8, respectively, p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…One of our recently published papers gives a detailed account of how mental stress can initiate and exacerbate events leading to vision loss in glaucoma. [58] This includes elevation in IOP, vascular dysregulation, endothelial dysfunction, and neurodegenerative processes. [58,88,89] Stress reduction may, therefore, be thought to be as one of the promising non-invasive and relatively inexpensive techniques to delay the onset of glaucoma and to bring down the severity.…”
Section: Glaucoma Where No Gene Is Known To Be Mutatedmentioning
confidence: 99%
“…[58] This includes elevation in IOP, vascular dysregulation, endothelial dysfunction, and neurodegenerative processes. [58,88,89] Stress reduction may, therefore, be thought to be as one of the promising non-invasive and relatively inexpensive techniques to delay the onset of glaucoma and to bring down the severity. In a clinical trial, we recently reported that mindfulness/ meditation-based stress reduction techniques lead to lowering of IOP and improve quality of life in glaucoma patients.…”
Section: Glaucoma Where No Gene Is Known To Be Mutatedmentioning
confidence: 99%
See 1 more Smart Citation
“…These psychological aspects can be interpreted as signs of excessive mental stress, with or without patients being aware of them. We recently argued that stress is not only the consequence but also a possible cause of vision loss [36]. It may be that patients with FS are overly burdened by excessive and long-term stress, and/or have lower stress resilience.…”
Section: Introductionmentioning
confidence: 99%